Organizational CommunicationOrganizational Communication, by Manning Peter K.. New York: Aldine de Gruyter, 1992, 249 pp., $19.95, paper. - Steckler, Nicole A. (Academy of Management Review, 1993)
The article reviews the book ?Organizational Communication,? by Peter K. Manning.